Techniques of Russian-Kazakh advertising translation (Eurasian Journal of Philology Science and Education, 2022)
The article considers the translation techniques of advertising texts and slogans of popular international brands from the Russian language into Kazakh. The functioning of structurally different languages in one space, their interaction and interpenetration are a unique material for studying translation strategies of advertisements. The impact of the Russian language on Kazakh is observed at all linguistic levels, since the ideology of the former Soviet Union adhered to the policy of using one common language for all peoples living on the territory of the country. Today in Kazakhstan the reforms on the revival of the Kazakh language are being actively implemented: a new Latin-based alphabet has been introduced and the question of the language ecology is being raised, trilingualism policy (Kazakh, Russian and English) is implemented. The research shows that all these factors influence the technical and linguistic characteristics of translation strategies of advertising texts, since advertising as a form of communication mirrors the culture of the nation, changes in the society and the level of economic development of the country. In the research the following translation methods were identified: borrowings, direct translation, semantic modulation, grammatical transposition, and equivalence. The analysis of translation strategies shows that the language of advertising is not characterized by the excessive use of stylistic devices and expressive means. The article studies the impact of globalization on the advertising market. Advertising videos and texts are not adapted to the national market, since Kazakhstan is integrating into the global economy. Key words: direct translation, oblique translation, advertising language, slogan, language ecology